The clubfoot over the centuries. Issue 2 (March 2017) - Sanzarello, Ilaria; Nanni, Matteo; Faldini, Cesare
Abstract : The aim of this paper is to review all treatment methods of the clubfoot over the years through the documentation present in the literature and art with the aim of better understanding the pathoanatomy of the deformity, but to also clarify factors that allow a safe, logical approach to clubfoot management. The initial part of this paper traces the most representative iconographic representations of clubfoot in history to describe how his presence was witnessed since ancient times. Hippocrates, the father of medicine, was the first to present written references about treatment methods of clubfoot. After the dark period of the Middle Ages, during the Renaissance, there were more detailed studies on the disease, with the creation of the first orthopedic orthotics, designed to correct the deformity with the help of famous names in medicine's history. In the XVIII century, as we witness the birth of orthopedics as a distinct discipline in medicine, more and more brilliant minds developed complex orthoses and footwear with the aim of obtaining a proper correction of the deformity. In the last part of the paper, there is a description of the main surgical techniques developed over the years until the return to conservative treatment methods such as the Ponseti method, internationally recognized as the gold standard of treatment, despite the presence of some unresolved issues such as the possible recurrence of the disease.